2013
DOI: 10.1002/pd.4050
|View full text |Cite
|
Sign up to set email alerts
|

First trimester maternal serum inhibin A concentrations in smokers

Abstract: Screening for trisomy 21 in pregnancy is commonly carried out in the first trimester at 10-13 completed gestational weeks, or in the second trimester at 14-20 weeks. Such gestational age windows have been chosen to profit from the most favourable discrimination in marker levels between affected and unaffected pregnancies. The performance of each maternal serum screening marker does not, however, switch on and off at a particular gestational week or day, rather it improves and declines gradually. Pregnancy asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
(20 reference statements)
0
1
0
Order By: Relevance
“…They recommended that a simple adjustment could be used to ensure that the screening performance of the quadruple test was similar among smokers and non‐smokers. Cowans and Spencer reported that the level of inhibin‐A in the first trimester of pregnancy was only around 10% higher among women who smoked compared with women who did not, which suggests that the difference increases with gestation and a single adjustment in the second trimester maybe too simplistic. Further, it has recently (personal communication) been suggested that the increase among women who smoke was not as high as 60%.…”
mentioning
confidence: 99%
“…They recommended that a simple adjustment could be used to ensure that the screening performance of the quadruple test was similar among smokers and non‐smokers. Cowans and Spencer reported that the level of inhibin‐A in the first trimester of pregnancy was only around 10% higher among women who smoked compared with women who did not, which suggests that the difference increases with gestation and a single adjustment in the second trimester maybe too simplistic. Further, it has recently (personal communication) been suggested that the increase among women who smoke was not as high as 60%.…”
mentioning
confidence: 99%